The 5′-Untranslated Region of the ntp303 Gene Strongly Enhances Translation during Pollen Tube Growth, But Not during Pollen Maturation - Hulzink, Raymond J.M. (American Society of Plant Physiologists, 2002)
Transcripts of the ntp303 gene accumulate abundantly throughout pollen development, whereas the protein only accumulates to detectable levels after pollen germination. In an attempt to explain the divergence in the accumulation profiles of the mRNA and the protein, we investigated the role of the untranslated regions (UTRs) in enhancing ntp303 translation during the transition from developing to germinating pollen. Luciferase reporter gene fusion constructs containing the ntp303 5′-UTR gave rise to luciferase activity that was up to 60-fold higher during pollen tube growth than that of constructs containing different 5′-UTRs. No apparent differences in the luciferase activity of these constructs were observed during pollen development. The ntp303 5′-UTR-mediated increase in luciferase activity was not significantly influenced by coding region or 3′-UTR sequences. Furthermore, enhanced luciferase activity directed by the ntp303 5′-UTR occurred predominantly at the post-transcriptional level. A series of 5′-UTR deletion constructs was created to identify putative regulatory sequences required for the high level of translation during pollen tube growth. Two predicted stem loop structures (H-I and H-II) caused a complete inhibition of the enhanced translation after their total or partial deletion. A (GAA)(8) repeat within the H-I stem loop structure was demonstrated to be important for the modulation of translation efficiency. The H-II stem loop structure was found to be essential for the determination of mRNA stability.